PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG PENGGUNAAN DAN PENGELOLAAN OBAT YANG RASIONAL MELALUI PENYULUHAN DAGUSIBU - Octavia, Devi Ristian; Susanti2, Irma; Mahaputra Kusuma Negara, Sri Bintang (P3M STIKES Aisyiyah Surakarta, 2020)
In the era of National Health Insurance (JKN) which has an impact on increasing people's motivation to check health at health care facilities, so that efforts to get drugs are quite easy. But the increasing use of drugs has not been supported by public knowledge about how to consume and manage medicines at home. This community service activity aims to increase public knowledge about the proper use of drugs (rational) and procedures for storing and disposing of drugs that have been damaged or expired properly. The method used in this service is to increase knowledge about Get Use of Save and Dispose of Medication (DAGUSIBU) PKK cadres by counseling or educating and mentoring drug management at home. The knowledge gained by the community in this activity is expected to change people's behavior in managing medicines at home and rational use of drugs. The method used in this service is by approach. From the results of evaluation and monitoring of activities that have been carried out shows a positive result, namely an increase in knowledge about rational drug use and proper management of medicines at home.